The impact of the COVID-19 pandemic on suicide ideation and suicide attempts in a sample of psychiatric inpatients. (September 2021) - Berardelli, Isabella; Sarubbi, Salvatore; Rogante, Elena; Cifrodelli, Mariarosaria; Erbuto, Denise; Innamorati, Marco; Lester, David; Pompili, Maurizio
Highlights: The impact of COVID-19 pandemic on vulnerable individuals may the lead to increased suicide risk. The aim of the present study was to see whether, in Italy, the frequency of suicidal ideation and suicide attempts differed in psychiatric patients before and during the COVID-19 pandemic and government lockdown restrictions. Results of the present study showed that suicide attempts, but not suicide ideation, were more frequent during the COVID-19 pandemic than before. Furthermore, mood disorder diagnoses were more frequent during the COVID-19 pandemic than before the pandemic. Abstract: There has been little research reported regarding both suicide ideation and suicide attempts during the COVID-19 pandemic and government lockdown restrictions in Italy, one of the countries most affected by the pandemic. We investigated whether the frequency of suicide ideation and suicide attempts differed between psychiatric patients admitted to a psychiatric unit before and during the COVID-19 pandemic and government lockdown restrictions. We also assessed psychiatric diagnosis, length of hospitalization, and types of admission. We collected data on 632 psychiatric patients admitted to a public psychiatric clinic. Patients were divided into two different groups according to their admission before or during the COVID-19 pandemic. Our results showed that only suicide attempts, but not suicide ideation, were more frequent in psychiatric patients admitted during the COVID-19 pandemic than before. Furthermore, mood disorder diagnoses were more frequent during the COVID-19 pandemic than before the pandemic. The types of admission and the mean length of hospitalization did not differ between the two groups. In conclusion the present study results adds consistent knowledge on the phenomenon of suicide during the challenging time of the pandemic, pointing to continuing effort in suicide prevention measures.